Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có : \(\frac{3\left(x^2+x-3\right)}{x^2+x-2}+\frac{x+3}{x+2}-\frac{x-2}{x-1}\)
\(=\frac{3\left(x^2+x-3\right)+\left(x+3\right)\left(x-1\right)-\left(x-2\right)\left(x-2\right)}{x^2+x-2}\)
\(=\frac{3x^2+3x-9+x^2+2x-3-x^2+4x-4}{x^2+x-2}\)
\(=\frac{3x^2+9x-16}{x^2+x-2}\)
`Answer:`
`a)`
`A=5(x+1)^2-3(x-3)^2-4(x^2-4)`
`=>A=5(x^2+2x+1)-3(x^2-6x+9)-4x^2+16`
`=>A=5x^2+10x+5-3x^2+18x-27-4x^2+16`
`=>A=(5x^2-3x^2-4x^2)+(10x+18x)+(5-27+16)`
`=>A=-2x^2+28x-6`
`b)`
`B=5(x+1)^2-3(x-3)^2-4(x+2)(x-2)`
`=2x(3x+5)-3(3x+5)-2x(x^2-4x+4)-[(2x)^2-3^2]`
`=6x^2+10x-9x-15-2x^3+8x^2-8x-4x^2+9`
`=(6x^2-4x^2+8x^2)-2x^3+(10x-9x-8x)+(-15+9)`
Thay `x=-7` vào ta được:
`B=10(-7)^2-2(-7)^3-7(-7)-6`
`=>B=10.49-2(-343)+49-6`
`=>B=490+686+49-6`
`=>B=1219`
a) (x+1)(x^2-x+1)-x^3
= x^3+1 - x^3 =1
b) (x-2)^2 -x(x+2)
= x^2 -4x+4-x^2-2x
=-6x+4
=-2(3x-2)
3.(x^4+x^2+1)-(x^2+x+1)^2=3.(x^4+2x^2+1-x^2)-(x^2+x+1)^2
=3.((x^2+1)^2-x^2)-(x^2+x+1)^2
=3.(x^2+x+1)(x^2-x+1)-(x^2+x+1)^2
=(x^2+x+1)(3.(x^2-x+1)-(x^2+x+1)
=(x^2+x+1)(2x^2-4x+2)
=(x^2+x+1)(căn 2 .x- căn 2)^2
\(\left(x+3\right)^2-\left(x-2\right)\left(x+2\right)=\left(x^2+6x+9\right)-\left(x^2-4\right)=x^2+6x+9-x^2+4=6x+13\)
( x + 3 )2 - ( x - 2 ) ( x + 2 )
= ( x2 + 6x + 9 ) - ( x2 - 4 )
= x2 + 6x + 9 - x2 + 4 = 6x + 13